2016
DOI: 10.1016/j.irfa.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The market valuation of M&A announcements in the United Kingdom

Abstract: This paper investigates the short-term market reaction to UK acquirers announcing domestic and foreign mergers and acquisitions (M&As) from 2000-2010. We define acquirers as value, moderate and glamour acquirers based on equally weighted market-to-book terciles. We find that value acquirers outperform glamour acquirers during and after the M&A announcement. We also focus on the impact of institutional ownership and find that higher domestic, foreign and total institutional ownership leads to lower market react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 99 publications
2
16
0
Order By: Relevance
“…Among the factors influencing the glamorous M&A, Andriosopoulos et al (2016) find indications about the possible role of company size in glamour acquisitions, suggesting that glamour acquirers are smaller in size, have lower leverage and higher cash ratios. In general, among the factors influencing the success of M&A, size is one of the included, well-studied ones (Akhigbe and Madura, 1999;Kallunki et al, 2009;Benou et al, 2007).…”
Section: Literature Review About Glamorous Manda Performance and Motivmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the factors influencing the glamorous M&A, Andriosopoulos et al (2016) find indications about the possible role of company size in glamour acquisitions, suggesting that glamour acquirers are smaller in size, have lower leverage and higher cash ratios. In general, among the factors influencing the success of M&A, size is one of the included, well-studied ones (Akhigbe and Madura, 1999;Kallunki et al, 2009;Benou et al, 2007).…”
Section: Literature Review About Glamorous Manda Performance and Motivmentioning
confidence: 99%
“…Regarding the analysis of motivations in glamour acquisitions, the reasons generally given to justify these operations, and their potential underperformance relative to value stocks in the long run, includes hubris and mispricing (Malmendier and Tate, 2008;Doukas and Petmezas, 2007). The positive expectation of future growth allows glamour acquirers to make value-decreasing acquisitions for which the market may not penalize them (Sudarsanam and Mahate, 2003;Andriosopoulos et al, 2016). This is in line with the hypothesis that managerial hubris plays an important role in the decision-making process of glamour acquirer firms when managers may be overconfident about their ability to manage an M&A deal.…”
Section: Literature Review About Glamorous Manda Performance and Motivmentioning
confidence: 99%
See 1 more Smart Citation
“…M&As are the most important economic events for firms because significant resources are devoted to capital investments (Anderson et al , 2017). Andriosopoulos et al (2016) and Cheng et al (2016) showed that information asymmetry may affect the market’s reactions to M&A announcements. For example, Cheng et al (2016) reported that information asymmetry is positively correlated with the cumulative ARs (CARs) around M&As announcements over five-day event windows.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…More specifically, Emery and Switzer (1999) showed that information acquirers exploit information asymmetry when selecting payment methods for investments that are expected to earn higher ARs. According to Andriosopoulos et al (2016), the choice of payment method for a M&A can significantly influence shareholders’ wealth at the time of the M&A announcement and also during the post-merger period. In the Canadian context, Jabbour et al (2000) reported that the ARs earned before an acquisition announcement are because of the corporate insiders’ actual trading.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%